Visual based SLAM using modified PSO - William, Low; Nagarajan, Ramachandran, Prof. Dr.; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher’s homepage at http://ieeexplore.ieee.org/